Head and neck abscessation and thrombophlebitis following cheek tooth extraction in a pony. (3rd March 2018) - Horbal, A. A.; Reardon, R. J. M.; Froydenlund, T.; Jago, R. C.; Dixon, P. M.
Summary: Due to their long hypsodont reserve crowns, extraction of equid cheek teeth can be difficult and result in more complications than the extraction of their shorter brachydont counterparts although the more recent resumption of oral extraction has greatly reduced such complications. The more common post‐extraction sequelae in equids include non‐healing alveoli due to retained dental or alveolar sequestrae which may lead to oromaxillary or oronasal fistula formation, chronic external sinus tract formation or osteomyelitis of the supporting bones. Collateral damage to adjacent teeth has also occasionally been reported during dental repulsion. Systemic complications following equine cheek tooth extraction have been infrequently described, including a small number of cases of exodontia‐related bacterial meningioencephalitis. This is surprising, as dental manipulation can lead to bacteraemia in many species, including horses. Infections at distant sites related to the spread of dental pathogens have been well described in humans and in small animals. This report describes deep abscessation of the masseter muscles followed by extensive thrombophlebitis of the jugular, facial and rostral cervical veins following oral cheek tooth extraction in a pony affected by pituitary pars intermedia dysfunction (PPID) that was successfully treated by abscess drainage and thrombectomy of the affected veins.